Diseño y validación del inventario de dependencia emocional – IDE - Aiquipa T., Jesús (2012)
The purpose of this research was to construct and validate an instrument to meet adequate psychometric properties to measure the emotional dependency. The total sample consisted of 757 participants from Lima-Peru (398 women and 359 men) aged between 18 and 55. Of total initial items were eliminated over 75% of them through systematic procedures, leaving the final test consisted of 49 items. The results show that Emotional Dependency Inventory - IDE has confiabiliadad indicators and evidence of adequate construct validity.